2016
DOI: 10.1002/brb3.506
|View full text |Cite
|
Sign up to set email alerts
|

Sex determines cortisol and alpha‐amylase responses to acute physical and psychosocial stress in patients with avoidant personality disorder

Abstract: IntroductionsAvoidant personality disorder (AVPD) has excessive and pervasive anxiety and discomfort in social situations. The aims of this study were to explore the relationship between AVPD and physical and psychological stress and psychological tests.MethodsWe evaluated 93 AVPD patients and 355 nonpatient controls by salivary amylase and cortisol responses during exposure to the Trier Social Stress Test (TSST) and electrical stimulation stress. Spielberger state‐trait anxiety inventory (STAI), Profile of Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
3
0
4
Order By: Relevance
“…Results showed that avoidant personality disorder symptoms were not associated with SBP reactivity under the low-and moderate-demand conditions and DBP reactivity under the low-demand condition but were associated with blunted SBP reactivity under the high-demand condition and blunted DBP reactivity under the moderate-and high-demand conditions. Based on previous research findings (Tanaka et al, 2016), this study further tested avoidant personality disorder symptoms in a nonclinical sample and their relation to cardiovascular reactivity in psychological stress tasks with three levels of cognitive demands (i.e., low, moderate, high). Our findings suggested that individuals with higher levels of avoidant personality disorder symptoms exhibited comparable cardiovascular reactivity in stress tasks with low cognitive demands but blunted cardiovascular reactivity in stress tasks with increased cognitive demands compared to those with lower levels of avoidant personality disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that avoidant personality disorder symptoms were not associated with SBP reactivity under the low-and moderate-demand conditions and DBP reactivity under the low-demand condition but were associated with blunted SBP reactivity under the high-demand condition and blunted DBP reactivity under the moderate-and high-demand conditions. Based on previous research findings (Tanaka et al, 2016), this study further tested avoidant personality disorder symptoms in a nonclinical sample and their relation to cardiovascular reactivity in psychological stress tasks with three levels of cognitive demands (i.e., low, moderate, high). Our findings suggested that individuals with higher levels of avoidant personality disorder symptoms exhibited comparable cardiovascular reactivity in stress tasks with low cognitive demands but blunted cardiovascular reactivity in stress tasks with increased cognitive demands compared to those with lower levels of avoidant personality disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research findings (Tanaka et al, 2016), this study further tested avoidant personality disorder symptoms in a nonclinical sample and their relation to cardiovascular reactivity in psychological stress tasks with three levels of cognitive demands (i.e., low, moderate, high). Our findings suggested that individuals with higher levels of avoidant personality disorder symptoms exhibited comparable cardiovascular reactivity in stress tasks with low cognitive demands but blunted cardiovascular reactivity in stress tasks with increased cognitive demands compared to those with lower levels of avoidant personality disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Test ten można przeprowadzić w różnych warunkach, a zadanie nie wymaga pozostawania bez ruchu, co jest konieczne w przypadku badań neuroobrazowych. Wykorzystywano go do oceny rekcji stresowej w grupie osób doświadczonych w medytacji [27], z unikającym zaburzeniem osobowości [28], o różnym chronotypie [29,30], różniących się pod względem postrzegania ryzyka społecznego [31], różnym postrzeganiem własnego ciała i poczuciem wstydu [32], z deprywacją snu [33], z grupy ryzyka rozwoju zaburzeń psychicznych [34], a także wśród kobiet w ciąży [35,36] lub osób mających trudne doświadczenia [37,38], z nadwagą [39,40], doświadczających wypalenia zawodowego [41], po próbach samobójczych [42] i uzależnionych od internetu lub hazardu [43,44].…”
Section: Trier Social Stress Test (Tsst)unclassified
“…Badania przeprowadzono w grupach osób z różnymi cechami osobowości w celu oceny wpływu tych cech na reaktywność organizmu na stresu wywołany procedurą TSST. Były to osoby z cechami osobowości unikającej [28], z różną tendencją do ruminacji [45] oraz o różnym natężeniu neurotyczności [46] i poziomie lęku [47].…”
Section: Trier Social Stress Test (Tsst)unclassified
See 1 more Smart Citation